MALAYSIAN HALAL CERTIFICATION: IT’S RELIGIOUS SIGNIFICANCE AND ECONOMIC VALUE - Shirin Asa, Rokshana (Jurnal Syariah, 2017)
Muslims consciously employ Shariah requirements in every aspect of their lives. It is their religious obligation to segregate between halal and haram. In the contemporary period, halal food is the most discussed matter around the world and the demand for it is on the rise. Taking this demand into consideration, the halal industry has become an important topic in Malaysia. The nation has standards and certification for halal, but the effectiveness of this system is dependent on a comprehensive and sound organizational structure. This study will examine how important the halal certification is in ensuring that the demand for halal food in Malaysia is met as well as the improvement of the halal industry and the extent halal certified food guarantee the rights of Malaysian Muslim consumers in compliance with Shariah principles. Presently, an issue relating to halal certification has become an important part of the industry. Malaysia is one of the pivotal and uprising stakeholders in the world’s halal market. For this reason, a comprehensive halal awareness programme is needed to point out the importance of halal certification, this will not only enhance the Malaysian halal industry, but also enrich the Malaysian economy